The Borden murders : Lizzie Borden & the trial of the century - Miller, Sarah, 1979- (Schwartz & Wade Books, 2016)
Examines the Borden murders, using newspaper articles to recreate the events and the trial and acquittal of Lizzie Borden and exploring Lizzie's story to theorize on what may have happened.